Adakah Persepsi Konsumen Dan Kualitas Produk Mempengaruhi Keputusan Pembelian Soes Legends? - Liliana Dewi; Quinta Marvellyn (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2020)
Soes Legends is a business that is engaged in the food and beverage industry that offers dried chocolate fill products. Based on the initial survey conducted by the author, the factors that dominate consumers in buying Soes Legends products are consumer perceptions and the quality of Soes products. The purpose of this study was to determine the effect of consumer perceptions and product quality on the decision to purchase Soes Legends products. The research method used is quantitative research with the sampling method is purposive sampling. The population in this study were all Soes Legends consumers who had repeated as many as 125 people with a sample of 96 people. The technique of collecting data uses a questionnaire with a Likert scale. The results of the questionnaire datawere analyzed to test factors and test variables using SPSS version 23. The results of this study indicate that consumer perceptions and product quality influence the decision to purchase Soes Legends products.